Fruitylicious: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
FRUITYLICIOUS is a business that was born out of the creative collaboration of fourindividuals who shared a passion for healthy and delicious food. They aimed to replaceconventional foods like peach mango pie with more exciting and innovative options, resultingin unique and flavorful dishes that were both nutritious and tasty.Fruitylicious projects a high return on investment (ROI) of 485.09%. This means that for everypeso invested in the business, an expected return of approximately 4.85 pesos is anticipated.While this indicates the potential profitability of the investment, it is important to consider otherfactors, such as risk and market conditions. The presentation emphasizes the need to assessand manage risks, respond to market dynamics, and evaluate non-financial factors for long-term success. Overall, Fruitylicious aims to capitalize on its projected ROI while remainingadaptable and focused on delivering high-quality, healthy desserts to customers.
Keywords: Business